Regioselective formal hydrocyanation of allenes: synthesis of β,γ-unsaturated nitriles with α-all-carbon quaternary centers - Lim, Seeun; Kim, Teresa; Lee, Yunmi (Beilstein Journal of Organic Chemistry, 2025)
This study introduces a highly selective hydrocyanation method based on copper-catalyzed hydroalumination of allenes with diisobutylaluminum hydride, followed by the regio- and stereoselective allylation with p-toluenesulfonyl cyanide. The proposed methodology is efficient for accessing acyclic β,γ-unsaturated nitriles with α-all-carbon quaternary centers and achieves yields up to 99% and excellent regio- and E-selectivity. The reaction proceeds under mild conditions and shows broad applicability to di- and trisubstituted allenes. Its practicality is demonstrated through the gram-scale synthesis and functional group transformations of amines, amides, and lactams, emphasizing its versatility and synthetic significance.
Keywords: α-quaternary nitrile; Cu catalysis; hydrocyanation; regioselectivity; tosyl cyanide